Deployment Of Remote-Access Openvpn Server With Aes-256 Bit Private Keys On Raspberry-Pi - Sudhir Dawra, Sher Jung, Manisha, Kushagra Singh (International Journal of Advanced Science and Technology, 2020)
Open, free Wi-Fi access points have increased rapidly with the advancement of technologies and trends. People prefer wireless connections wherever possible to access the internet and the intranet which introduces high portability. It has become necessity for employees to stay connected with their organization from remote locations to go with the workflow without compromising the security. This paper assumes a level of trust in ISPs (Internet Service Providers) and they comply with their respective laws of the country in respect of the illegal interception of confidential and private information. This paper presents an alternative in the form of a VPN deployment. It deploys the rather inexpensive Raspberry Pi (RPi) equipment in association with open-source OpenVPN software which supports the server as well as the client and uses the latest AES(Advanced Encryption Standard)-256 bit private key rather than the old 3DES(Triple Data Encryption Standard).The deployment requires less alterations in the existing small office/organization network and is easy to configure on various platforms including Windows, OS X, Linux, iOS and Android.